The Influence of Discipline, Work Environment, and Work Commitment on Job Satisfaction - Sherly Ong; Hendry Hendry; Vivi Winata; Monika Monika (International Journal of Social Science and Business, 2021)
This study aims to analyze discipline, work environment, and commitment to job satisfaction. This type of research is quantitative research. The population in this study found 66 employees. The number of samples in this study was 66 employees. In this study, data collection related to the problems studied by researchers was carried out through questionnaires distributed to employees at the company, interviews were conducted to employees, and documentation studies in the form of company data, books, and journals related to the variables studied. Sources of research data consist of primary data in this study are interviews and questionnaires and secondary data is data obtained from notes, books, and magazines in the form of financial reports for company publications, government reports, articles, books as theory, magazines, and so on. The data analysis used is classical assumption test and hypothesis testing. The results showed that the coefficient of determination can be seen from the Adjusted R Square value of 0.561, meaning that 56.1% of the variation in job satisfaction variables can be explained by variations in work discipline, work environment, and commitment variables. while the remaining 43.9% is explained by other variables not examined in the study. So, it can be concluded that discipline, work environment, and work commitment have a positive effect on job satisfaction.